PENGARUH KUALITAS AUDIT DAN KEPEMILIKAN INSTITUSIONAL TERHADAP COST OF DEBT (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2012-2015) - Robiansyah, Anton; Novita, Dwi; Ranidiah, Furqonti (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2019)
Anton Robiansyah, Dwi Novita, Furqonti Ranidiah; This study aims to analyze the effect of audit quality and institutional ownership on the cost of debt. The population in this study are all manufacturing companies listed on the Stock Exchange in 2011-2014. The type of research used in this study is empirical research. The sampling technique used was purposive sample and selected 72 unit analysis companies. The data analysis tool in this test uses OLS (ordinary least square), which wants to see the effect of audit quality and institutional ownership on the cost of debt.Based on the results of this study indicate that audit quality has a negative effect on the cost of debt with a significance level of 0.014 which means that the company that chooses the BIG4 KAP has a good reputation and this is seen as a positive thing for the creditor. Whereas institutional ownership does not affect the cost of debt with a significance level of 0.847 indicating that the presence or absence of institutional ownership of companies - companies in Indonesia does not affect the institutional ownership relationship and the cost of debt.